Evaluation of a commercial ELISA for serodiagnosis of Helicobacter pylori infection. Issue 4 (April 1991) - Crabtree, J E; Shallcross, T M; Heatley, R V; Wyatt, J I
Abstract : A commercial ELISA for the detection of Helicobacter pylori IgG antibodies was evaluated using serum from 242 patients attending an endoscopy clinic. The efficacy of the ELISA was assessed in relation to the histological detection of H pylori on antral mucosal biopsy specimens. In patients under 61 years of age (n = 138) the ELISA was 97.5% sensitive and 85.5% specific for H pylori infection, with a positive predictive value of 91% and a negative predictive value of 96%. Over the whole group the sensitivity of the ELISA was 93.8% and the specificity 79.3%. The positive predictive value and negative predictive values were, respectively, 90% and 87%. These results suggest that the Bio-Rad GAP IgG H pylori ELISA is suitable for serodiagnosis of H pylori infections for most clinical purposes and thus makes H pylori serology available to routine diagnostic laboratories.